Mass Balance and Energy Balance at Strandline Glacier (Terra Nova Bay, Antarctica): Methods and Preliminary Results - Giorgio Vassena; Claudio Smiraglia; Guglielmina Diolaiuti; Michele Motta (2002)
Intensive fieldwork was carried out during the 16'" Italian Campaign in Antarctica (2000-2001) with the intention of completing the groundwork required for calculating the mass balance and energy balance of several local glaciers in northern Victoria Land. The studied glaciers are of limited size and have well-defined profiles, with elongated, convex terminal tongues. The glacier tongues form a clearly delimited frontal scarp, although the exact position of the front is generally concealed by a mantle of snow and ice (i.e. apron). Data-collection methods and preliminary results for Strandline Glacier, located in the vicinity of the Italian station at Terra Nova Bay, are discussed in this report. Strandline Glacier is characterized by distinct areas of accumulation and ablation: substantial snow accumulation occurs along its borders, deflation in the middle sector. The lower portion of the latter area forms a prominent tongue which terminates in a cliff, where ablation mainly consists of dry calving, as shown by the blocks of ice lying at the base of the cliff which feed an apron (Baroni & Orombelli, 1987; Chinn et al., 1989)